Correction: Compositional engineering of the pi-conjugated small molecular VOPcPhO : Alq3 complex to boost humidity sensing. Issue 41 (12th May 2017) - Fatima, Noshin; Aziz, Fakhra; Ahmad, Zubair; Najeeb, M. A.; Azmeer, M. I.; Karimov, Kh. S.; Ahmed, M. M.; Bashir, S.; Shakoor, R. A.; Sulaiman, K.
Abstract : Correction for 'Compositional engineering of the pi-conjugated small molecular VOPcPhO : Alq3 complex to boost humidity sensing' by Noshin Fatima et al., RSC Adv., 2017, 7, 19780–19786.